PREPARATION FOR THE RESEARCH CONDUCTING UNDER THE PROGRAMME «INTERDISCIPLINARY INDIVIDUAL STUDIES» IN POLAND - Kateryna Kuzan (Pavlo Tychyna Uman State Pedagogical University, 2017)
The article is devoted to innovative training program «Interdisciplinary Individual Studies», which has been successfully implemented in Poland since 1991. Based on the analysis of legislative and regulatory documents, the basic principles of the program functioning in higher education in Poland have been revealed. It was stated that the above mentioned training program includes a broad interdisciplinary training, which is an integral part of research activities of students. Attention is paid to the characteristics and nature of research activities of students within interdisciplinary individual studies. The content, forms and methods of formation of students' readiness to scientific research have been defined. The basic research skills that students acquire in a result of theoretical and practical training have been outlined. It is noted that the organization and content of students training to research in the framework of the «Interdisciplinary individual studies» based on autonomy in education and creative scientific activity. As a result, research skills are formed and allow students think outside of the box to solve problems. The importance of interdisciplinary training for disclosure of students' creative scientific potential has been grounded.